UAV Sensors for Environmental Monitoring - Felipe Gonzalez Toro (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The rapid development and growth of UAVs as a remote sensing platform, as well as advances in the miniaturization of instrumentation and data systems, are catalyzing a renaissance in remote sensing in a variety of fields and disciplines from precision agriculture to ecology, atmospheric research, and disaster response. This Special Issue was open for submissions that highlight advances in the development and use of sensors deployed on UAVs. Topics include, but were not limited, to: • Optical, multi-spectral, hyperspectral, laser, and optical SAR technologies • Gas analyzers and sensors • Artificial intelligence and data mining based strategies from UAVs • UAV onboard data storage, transmission, and retrieval • Collaborative strategies and mechanisms to control multiple UAVs and sensor networks • UAV sensor applications: precision agriculture; pest detection, forestry, mammal species tracking search and rescue; target tracking, the monitoring of the atmosphere; chemical, biological, and natural disaster phenomena; fire prevention, flood prevention; volcanic monitoring, pollution monitoring, micro-climates and land use